FARMER SATISFACTION WITH THE FARMER CARD PROGRAM IN KENDAL REGENCY, CENTRAL JAVA - Mukson, Mukson; Ekowati, Titik; Prasetyo, Edy; Handayani, Migie (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The subsidized fertilizer distribution program through farmer card (Kartu Tani), initiated since 2016, requires evaluation and improvement in its implementation. The use of subsidized fertilizers must be precise in its dose and timing in order to increase productivity. The purpose of this study is to analyze the level of satisfaction of farmers with the farmer cardprogram related to subsidized fertilizers. This research employs the survey method. The location was determined by purposive sampling with five urban villages based on the number of distributed cards and each of them represents three regions; lowlands, midlands, and uplands. The respondents to this study were 100 people; 20 people from each urban village were selected using the random sampling method. The data were taken using the interview method based on questionnaires distributed to farmers. The collected data was then analyzed using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The results showed that most of the farmers who received the card in Kendal Regency were predominantly male, had high school education, and with an average land ownership of 0.5-1.0 hectares. The IPA analysis showed that in quadrant I (8 attributes need improvement), quadrant II (there are 16 achievement attributes that need to be maintained), quadrant III (11 low priority attributes) and quadrant IV (7 redundant attributes). Farmers' satisfaction with the farmer card program is at 71.69%, which is in the range of 61%-80.99%. In other words, the farmers are satisfied with the farmer ard services provided by the government.